The Responses of the Ribonuclease A Superfamily to Urinary Tract Infection - Becknell, Brian (Front Immunol, 2019)
The lower urinary tract is routinely exposed to microbes residing in the gastrointestinal tract, yet the urothelium resists invasive infections by gut microorganisms. This infection resistance is attributed to innate defenses in the bladder urothelium, kidney epithelium, and resident or circulating immune cells. In recent years, surmounting evidence suggests that these cell types produce and secrete soluble host defense peptides, including members of the Ribonuclease (RNase) A Superfamily, to combat invasive bacterial challenge. While some of these peptides, including RNase 4 and RNase 7, are abundantly produced by epithelial cells, the expression of others, like RNase 3 and RNase 6, increase at infection sites with immune cell recruitment. The objective of this mini-review is to highlight recent evidence showing the biological importance and responses of RNase A Superfamily members to infection in the kidney and bladder.